Ceremonial science: The state of Russian economics seen through the lens of the work of 'Doctor of Science' candidates - Alexander Libman; Joachim Zweynert (Institut für Ost- und Südosteuropaforschung (IOS), 2014)
The paper investigates the current status of economic research in Russia using a previously unexplored dataset of Russian 'Doctor of Science' (Dr. Sc.) theses. The Dr. Sc. degree is a postdoctoral qualification necessary for career advancement at most Russian universities. Thus, by looking at the Dr. Sc. theses we are able to provide a systematic overview of 'average' scientific standards in Russia, particularly at the mass universities at which most administrators and bureaucrats are trained. We show that the level of integration of Russian economics into the international scientific community remains very low. Moreover, we obtain a picture of a mostly 'ceremonial' science. Researchers combine references to 'classical' research, formal methods and practical application merely as an instrument for presenting the mostly verbal argument in a more 'scientific' way.
urn:nbn:de:101:1-2014012113917
Keywords: A11; B41; I23; P39; 330; Russian economics; international integration; scientific methodology